1985
DOI: 10.1021/jm00147a025
|View full text |Cite
|
Sign up to set email alerts
|

Potential neuroleptic agents. 3. Chemistry and antidopaminergic properties of substituted 6-methoxysalicylamides

Abstract: A series of substituted 6-methoxysalicylamides were synthesized from their corresponding 2,6-dimethoxybenzamides by demethylation of one methoxy group with boron tribromide. Substituted 6-methoxysalicylamides having a lipophilic aromatic substituent in the 3-position para with respect to the methoxy group, e.g. a bromo or an iodo atom or an ethyl or a propyl group, and having an (S)-N-(1-alkyl-2-pyrrolidinyl)methyl moiety as the side chain were found to be potent blockers of [3H]spiperone binding in vitro and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

1985
1985
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(52 citation statements)
references
References 0 publications
2
50
0
Order By: Relevance
“…As stated above, eticlopride was nine times more potent than haloperidol at inhibiting H AI ; however, eticlopride and haloperidol were nearly equipotent at inhibiting S AI , and haloperidol was equipotent in both assays [31,33]. This same phenomenon of separation between inhibition potencies was true for the earlier generation benzamides [45,46] as well as for the more potent 3‐alkyl‐substituted salicylamides [21]; each inhibited H AI at lower doses than required to inhibit S AI . Interestingly, a binding displacement study showed that high doses of sulpiride, which inhibited both H AI and S AI , displaced [ 3 H]spiperone to the same extent in all brain regions studied [47].…”
Section: Developmentmentioning
confidence: 87%
“…As stated above, eticlopride was nine times more potent than haloperidol at inhibiting H AI ; however, eticlopride and haloperidol were nearly equipotent at inhibiting S AI , and haloperidol was equipotent in both assays [31,33]. This same phenomenon of separation between inhibition potencies was true for the earlier generation benzamides [45,46] as well as for the more potent 3‐alkyl‐substituted salicylamides [21]; each inhibited H AI at lower doses than required to inhibit S AI . Interestingly, a binding displacement study showed that high doses of sulpiride, which inhibited both H AI and S AI , displaced [ 3 H]spiperone to the same extent in all brain regions studied [47].…”
Section: Developmentmentioning
confidence: 87%
“…The radiotracer was synthesized at the Austrian Research Center Seibersdorf, Austria, and subsequently brought to the nuclear medical facility of the University of Vienna by ground transportation within 90 min. For the synthesis of S(-)-and R(+)IBZM, a modification of the original method described by de Paulis (de Paulis et al 1985) was used. Electrophylic iodination was performed with [ 123 I]NaI (0.08 nmol/mCi), using peroxyacetic acid as oxidant and 0.01 M HCl as solvent.…”
Section: Spect Investigationmentioning
confidence: 99%
“…The dopaminergic D 3 receptor belongs to the class A family of GPCRs and has attracted recently great interest as a potential drug target for unmet therapeutic needs like cognitive impairment in schizophrenia, and drug abuse 10. Eticlopride is a substituted benzamide analog11, 12 showing high affinity and selectivity for dopamine D 2 ‐like receptors 13. Initially, it was developed as a potential antipsychotic agent but is now mainly applied for pharmacological research.…”
Section: Introductionmentioning
confidence: 99%